Evaluation of Srivastava index to distinguishing Beta-Thalassemia Trait from Iron Deficiency - Hassnain Shahid, Maryam Saleem, Nauman Naseer, Samina Tabussam, Atif Aziz, Saeed Ullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assist in the differential diagnosis of beta thalassemia trait and iron deficiency anaemia, many alternative red blood cell index-based formulae were examined. Methods: The Rawalpindi PEMH performed this study from June 2021 to March 2022. For individuals with beta- thalassemia trait and iron deficient anaemia, age and gender were not considered. More than five millilitres of blood were drawn from each patient in order to determine the haemoglobin content, the number of red blood cells, how they were distributed, and the average cell volume. Five alternative formulas may be used to differentiate these two circumstances. Shine and Lal index, Mentzer index, Srivastava index and Green & King index are among the most well- known ones. Youden's index was included in the calculation of sensitivity, specificity, and positive and negative predictive values (PPVs). Results: The iron deficiency anaemia rate was 70%, and the beta thalassemia phenotype was 30% among the 1500 participants. This indicator has a sensitivity of 100% and specificity of 93.3% when it comes to discriminating between beta-thalassemia trait and iron deficiency anaemia. Conclusion: The red cell distribution width index may be used to differentiate between beta thalassemia trait and iron deficiency anaemia. If a haemoglobin electrophoresis is not available, a diagnosis of beta thalassemia may still be made.